Twin boundary-accelerated ferritization of austenitic stainless steels in liquid lead–bismuth eutectic. (June 2016) - Hosemann, P.; Frazer, D.; Stergar, E.; Lambrinou, K.
Abstract: Exposure of austenitic stainless steels to liquid lead–bismuth eutectic with low concentration of dissolved oxygen typically results in selective leaching of highly-soluble alloying elements and ferritization of the dissolution-affected zone. In this work, focused ion beam, transmission electron backscatter diffraction and scanning transmission electron microscopy were utilized to elucidate early-stage aspects of the dissolution corrosion process of cold-worked austenitic stainless steels exposed to static, oxygen-poor liquid lead–bismuth eutectic at 450 °C for 1000 h. It was found that deformation-induced twin boundaries in the cold-worked steel bulk provide paths of accelerated penetration of the liquid metal into the steel bulk. Graphical abstract: